Cognitive Enhancement Therapy in Schizophrenia - Zain Budi Syulthoni; I Gusti Ngurah Gunadi (Jurnal Psikiatri Surabaya, 2020)
Schizophrenia is a chronic, severe, and debilitate mental disorder that causing disability. Factors that causing disability is cognitive impairment. Cognitive impairment caused by disturbance in neurodevelopmental process of the brain that related to Dopaminergic, GABA-ergic, and Acethylcholinergic pathway. Cognitive Enhancement Therapy is additional therapy to recovery the cognitive function. CET facilitated repairmenin socio and non-socio cognitive function, encourage patient behaviour related social condition, develop patient understanding of schizophrenia and the impact on cognitive impair- ment, and rehabilitation program that characterised of an experiential and exercise to repair the non-social cognitive function (attention, memmory, and problem solving). CET shows improvement in early or late onset of schizophrenia. Pa- tients who got CET can back to work. Now, CET is used for early intervention in cognitive impairment in Schizophrenia. CET was also developed in patients with Schizoaffective, Schizophrenia comorbid with drug abuse, and patientswith au- tism. Hopefully, the improvement onquality of life patient with schizophrenia can achieve with combination pharmacother- apy and Cognitive Enhancement Therapy.